PRÁXIS DOCENTE POMERANA: CULTURA, LÍNGUA E ETNICIDADE - Dettmann, Jandira Marquardt (2020)
This article analyses how the Pomeranian Language teachers' praxis contributes to promoting the culture of the Traditional Pomeranian People in a bilingual context. Developed in Santa Maria de Jetibá, Espírito Santo, Brazil, it brings up questions about t